Community Participation And Solid Waste Management In Urban Councils: A Case Of Masaka Municipal Council - Luyimbazi, James; Nabaho, Lazarus (My University, 2015)
The inability of municipalities to handle the increasing amount of waste generated is a growing problem in most developing countries. The study examined how community participation affected solid waste management in Urban Councils, a case study of Masaka Municipal council. A theoretical framework was developed employing the Institutional Theory and the Waste Management Theory, which were used as a basis to compare theoretical and actual practices when analyzing waste management practices in municipalities. The report shows that despite some hurdles, there are some municipalities which have addressed the waste management problem using community participation in their localities. Both qualitative and quantitative approaches were been used to obtain data that was analyzed to obtain key findings based on specific objectives that included: a positive correlation results for planning (.179**), implementation (.595**) and M&E (.431**) on Solid Waste Management. Findings indicated that there was very low community participation at the planning level and very poor community participation at the implementation and Monitoring and Evaluation levels to contribute to effective solid
Keywords: solid waste management; Urban Councils